Phosphatidic acid phosphatase LPIN1 in phospholipid metabolism and stemness in hematopoiesis and AML - Huber, Karin; Garg, Swati; Schlautmann, Lena P.; Wang, Rui; He, Lixiazi; Huth, Richard; Pouya, Alireza; Rohde, Christian; Janssen, Maike; Lüchtenborg, Christian; Arnold, Christian; Luque-Navarro, Pilar M.; et al. (HemaSphere, 2025)
Targeting metabolism represents a promising approach to eradicate leukemic stem cells (LSCs) that are considered critical drivers of relapse in acute myeloid leukemia (AML). In this study, we demonstrate that the phosphatidic acid phosphatase LPIN1, which regulates the synthesis of diacylglycerol, the key substrate for triacylglycerol, and phospholipid production, is crucial for the function of healthy and leukemic hematopoietic stem and progenitor cells (HSPC and LSC). LPIN1 mRNA was highly expressed in the CD34+ compartment of primary human AML samples. LPIN1 suppression inhibited the proliferation of primary leukemic cells and normal HSPCs in vitro and in xenotransplantation assays. Lipidomics analyses revealed a reduction of phosphatidylcholine (PC) and phosphatidylethanolamine and an upregulation of sphingomyelin upon LPIN1 depletion. Distinct phospholipid composition was associated with genetic AML groups, and targeting PC production by choline kinase inhibitors showed strong anti-leukemic activity. In summary, our data establish a regulatory role of LPIN1 in HSPC and LSC function and provide novel insights into the role of glycerophospholipid homeostasis in stemness and differentiation.